Effectiveness of Myotherapy on Stress among Patients Subjected to Major Orthopaedic Surgery at a Tertiary Care Hospital, South India (Indian Journal of Public Health Research & Development, 2020)
Introduction: The stress response to surgery, critical illness, trauma, and burns encompasses derangementsof metabolic and physiological processes which induce perturbations in the inflammatory, acute phase,hormonal, and genomic responses. The surgery-induced stress response is largely similar to that triggeredby traumatic injuries, the duration of the stress response, however, varies according to the severity of injury.Objectives: The objectives of the study were to determine the effectiveness of myotherapy on stress andassociate the selected background variables with stress.Method: The research design adopted for the study was randomized controlled trial. The study wasconducted among 250 samples,125 in the study and 125 in control group to evaluate the effectiveness ofmyotherapy on stress among patients subjected to major orthopedic surgeries. The mean age of the studyparticipants were male and female equally distributed. Data were collected and analyzed using descriptiveand inferential statistics.Findings: Independent t ‘t’ test revealed that mean difference score was observed in stress at p=0.001 level.Post stress in the study group was significantly associated within previous history of hospitalization at thelevel of p
Keywords: Stress. Myotherapy, post operative, surgery.